Stylistic Peculiarities of Contextual Hyperbole in Sherwood Anderson’s “The Book of the Grotesque” and “Godliness” - Kojoyan, Ani (Armenian Folia Anglistika, 2010)
The article aims to investigate the stylistic characteristics of hyperbole in Sherwood Anderson’s short stories. The examination of the theoretical part of the given material and the analysis of the examples make it possible to distinguish three major types of contextual hyperbole in the short stories – mixed hyperbole, non-mixed hyperbole and biblical allusive hyperbole.